Confining Sn nanoparticles in interconnected N-doped hollow carbon spheres as hierarchical zincophilic fibers for dendrite-free Zn metal anodes - Yu, Huan (2022)
We developed a three-dimensional hybrid fiber host consisting of interconnected N-doped hollow carbon spheres embedded with Sn nanoparticles (denoted as Sn@NHCF) for Zn metal anodes in high-performance Zn metal batteries. Experimental observations and density functional theory calculation reveal that the zincophilic Sn nanoparticles and N-doped carbons enable the homogeneous Zn deposition on the interior and exterior surfaces of the hollow fibers. Moreover, the hierarchical hollow fiber network effectively reduces the structural stress during the plating/stripping process. As a result, the developed Sn@NHCF host exhibits remarkable electrochemical properties in terms of high Coulombic efficiency, low voltage hysteresis, and prolonged cycling stability without dendrite formation. Moreover, a full cell based on the designed Sn@NHCF-Zn composite anode and a V2O5 cathode demonstrates superior rate capability and stable cycle life. This work provides a new strategy for the design of dendrite-free Zn anodes for practical applications.